Инглиззабон мамлакатларда ўзбек тилининг ўрганилиши, тадқиқи қилиниши - sodiqov, omon (FILOLOGIYA UFQLARI JURNALI, 2021)
The article discusses the current role of the Uzbek language and measures for the development of the Uzbek language , as well as the study of the Uzbek language in English –speaking countries.